Antibacterial activity of jamblang leaf ethanol extract (Syzygium cumini) against the growth of Propionibacterium acnes - Maria Fransiska Priska Yulianti; Anita Lidesna Shinta Amat; Regina Marvina Hutasoit; Prisca Deviani Pakan (Indonesian Society for Biochemistry and Molecular Biology, 2023)
Background: Propionibacterium acnes is a bacterium found on the skin that plays a significant role in acne vulgaris. The inappropriate use of antibiotics can lead to resistance, necessitating the search for alternative therapies from plants with high antibacterial potential. One such plant is jamblang (Syzygium cumini), which has demonstrated antibacterial properties. Objective: This research aims to test the antibacterial activity of jamblang leaf extract against the growth of P. acnes. Method: The study employed an experimental design with a posttest-only control group design. The treatment groups consisted of a positive control (clindamycin), a negative control (sterile distilled water), and jamblang leaf extract groups with concentrations of 100%, 50%, 25%, 12.5%, and 6.25% (n=4). Data analysis was conducted using the One-Way ANOVA statistical test. Results: The jamblang leaf extract exhibited antibacterial potential against the growth of P. acnes. The extract showed strong antibacterial activity at concentrations of 100%, 50%, 25%, and 12.5%, and moderate antibacterial activity at a concentration of 6.25%. Conclusion: This suggests that jamblang leaf extract could be a promising alternative therapy for treating acne vulgaris, offering a natural solution to combat antibiotic resistance.